2014
DOI: 10.1016/j.jcis.2013.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and numerical study of the electro-osmotic annular flow of viscoelastic fluids

Abstract: a b s t r a c tIn this work we present semi-analytical solutions for the electro-osmotic annular flow of viscoelastic fluids modeled by the Linear and Exponential PTT models. The viscoelastic fluid flows in the axial direction between two concentric cylinders under the combined influences of electrokinetic and pressure forcings. The analysis invokes the Debye-Hückel approximation and includes the limit case of pure electro-osmotic flow. The solution is valid for both no slip and slip velocity at the walls and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 30 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…For viscoelastic fluid with mixed pressure-electroosmotic driving force, Park et al [ 30 ] also investigated viscoelastic EOF in a microchannel. Afonso et al [ 31 , 32 ] reported analytical solutions for EOF of viscoelastic fluid in a microchannel and between two concentric cylinders using the PTT model and Finitely Extensible Nonlinear Elastic with Peterlin closure (FENE-P) model. Based on the earlier work, Afonso et al [ 33 ] also investigated the EOF of viscoelastic fluid in a microchannel with asymmetric zeta potential, and Sousa et al [ 34 ] derived an analytical solution taking into account the wall depleted layer.…”
Section: Introductionmentioning
confidence: 99%
“…For viscoelastic fluid with mixed pressure-electroosmotic driving force, Park et al [ 30 ] also investigated viscoelastic EOF in a microchannel. Afonso et al [ 31 , 32 ] reported analytical solutions for EOF of viscoelastic fluid in a microchannel and between two concentric cylinders using the PTT model and Finitely Extensible Nonlinear Elastic with Peterlin closure (FENE-P) model. Based on the earlier work, Afonso et al [ 33 ] also investigated the EOF of viscoelastic fluid in a microchannel with asymmetric zeta potential, and Sousa et al [ 34 ] derived an analytical solution taking into account the wall depleted layer.…”
Section: Introductionmentioning
confidence: 99%
“…The power‐law model was also used in the literatures and , in which the analytical solution for velocity distribution of the electroosmosis flow in a slit microchannel is obtained. Furthermore, in the analytical and numerical study on electroosmotic flow of viscoelastic fluid, Maxwell fluid model , Oldroyd‐B model , and the Phan–Thien–Tanner fluid model were also extensively considered to describe the rheological behavior of fluids. The experimental study on electroosmotic flow of non‐Newtonian fluids can also be found in .…”
Section: Introductionmentioning
confidence: 99%
“…In most of the research on the electroosmotic flow, the analytical expression of electrostatic potential distribution in electric double layer (EDL) can be obtained by using the Debye–Hückel linear approximation, which was proposed by Debye‐Hückel in 1923, to linearize the Poisson–Boltzmann equation . It is worthy of mentioning here that their analysis is valid only for a low surface potential (ζ < 25 mV).…”
Section: Introductionmentioning
confidence: 99%
“…Berli et al [27] used a simple power-law model to analyze the electrokinetic flow of through slit and cylindrical microchannels, deriving expressions for flow rate and electric current as functions of the simultaneously applied electric potential and pressure gradients. Ferrás et al [28] employed linear and exponential PTT viscoelastic models to derive semi-analytical solutions for the electro-osmotic annular flow of non-Newtonian liquids. They considered both no slip and slip boundary conditions.…”
Section: Introductionmentioning
confidence: 99%